1999
DOI: 10.1001/archpsyc.56.6.507
|View full text |Cite
|
Sign up to set email alerts
|

A National Evaluation of Treatment Outcomes for Cocaine Dependence

Abstract: Patients with the most severe problems were more likely to enter long-term residential programs, and better outcomes were reported by those treated 90 days or longer. Dimensions of psychosocial problem severity and length of stay are, therefore, important considerations in the treatment of cocaine dependence. Cocaine relapse rates for patients with few problems at program intake were most favorable across all treatment conditions, but better outcomes for patients with medium- to high-level problems were depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
215
1
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(236 citation statements)
references
References 25 publications
12
215
1
8
Order By: Relevance
“…Staff working in private treatment organizations tended to have masters degrees, and, overall, the programs tended to employ a number of part-time or contractual staff to run individual programs. The DATOS findings indicate that typical out-patient programs were similar to the drug court treatment programs described earlier in that they included a mix of approaches with a focus on psychosocial education group counseling sessions and tended to be eclectic in the therapies that they provided (Simpson, Joe, Fletcher, Hubbard, & Anglin, 1997).…”
Section: Drug Treatment For Offenders In the Community Public Health mentioning
confidence: 68%
“…Staff working in private treatment organizations tended to have masters degrees, and, overall, the programs tended to employ a number of part-time or contractual staff to run individual programs. The DATOS findings indicate that typical out-patient programs were similar to the drug court treatment programs described earlier in that they included a mix of approaches with a focus on psychosocial education group counseling sessions and tended to be eclectic in the therapies that they provided (Simpson, Joe, Fletcher, Hubbard, & Anglin, 1997).…”
Section: Drug Treatment For Offenders In the Community Public Health mentioning
confidence: 68%
“…The major goal of the therapeutic community is to encourage and support social learning, which fosters changes in behavior and attitude and the more elusive phenomenon of change in world view and self-image (De Leon, 2000). Studies have shown that individuals who complete therapeutic community treatment have lower levels of substance use, criminal behavior, unemployment, and depression than they had prior to treatment (Martin, Butzin, Saum, & Inciardi, 1999;Simpson, Joe, & Brown, 1997;Simpson, Joe, Fletcher, Hubbard, & Anglin, 1999;Wexler, Melnick, Lower, & Peters, 1999).…”
Section: Therapeutic Communitiesmentioning
confidence: 99%
“…Pharmacologic treatment trials for cocaine dependence report dropout rates of 0-84% (de Lima et al, 2004). Psychotherapy treatment trials for cocaine dependence report dropout rates of 29-41% (Kang et al, 1991;Simpson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%